Manajemen Pelayanan Kesehatan Asuhan Kebidanan Di Puskesmas Sekip Palembang Tahun 2024 - Riska Widya Astuti; Ike Sri Wahyuni; Bulan Purnamasari; Dwi Astuti (Al-Su’aibah Midwifery Journal, 2024)
Community Health Centers (Puskesmas) are health service facilities that carry out public health efforts and first-level individual health efforts by prioritizing promotive and preventive efforts. To ensure that Puskesmas activities are carried out in accordance with the principles and functions of good management, the government has prepared guidelines for Puskesmas management as stated in PMK No. 44 of 2016 concerning Community Health Center Management Guidelines. Sekip Community Health Center as a Community Health Center which has a working area in several areas of Kemuning sub-district also implements management functions as written in PMK No. 44 of 2016. However, in its implementation there are several obstacles such as less than optimal HR planning and there are still Community Health Center service programs that have not yet achieved SPM targets especially in the Maternal and Child Health Room. A study of data on midwifery management practices in the KIA/KB room found several problems, including: Low VIA examination visits which were still far below the SPM target, namely only 14.92% with an SPM target of 100%, obstetric complications by the community which also had not reached the SPM target, namely 92.21 % in 2023, as well as the still low coverage of K6 visits which also has not reached the SPM target, namely 99.87% in 2023. By finding solutions to priority problems, it is hoped that it will be able to increase the number of KIA program coverage that has not reached the SPM target. It is recommended that the Sekip Community Health Center be more focused and able to attract public interest in midwifery management in the KIA/KB room, especially in several areas that have not yet reached the SPM target